2022
DOI: 10.46517/seamej.v12i2.198
|View full text |Cite
|
Sign up to set email alerts
|

The Questioning Techniques of Primary School Mathematics Teachers in their Journey to Incorporate Dialogic Teaching

Abstract: Questioning is one of the critical repertoires in dialogic teaching. Teachers who set dialogic classrooms need to be able to use questioning effectively. Effective questioning techniques by teachers improve teacher-student instructional dialogues in primary school mathematics classrooms. In this study, the questioning practices of three primary school mathematics teachers were analysed in their journey to incorporate dialogic teaching. Data were gathered through lesson observations, video recordings and teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…These practices involve providing feedback to modify and improve teaching and learning (assessment for learning), students' self and peer assessment (assessment as learning), and judging students' mastery at the end of the instructional period (assessment of learning) (Glazer, 2014;Yan and Brown, 2021;Baidoo-Anu et al, 2023a). Key assessment practices include effective questioning, sharing learning intentions and success criteria with students, and using summative assessment for formative purposes (Moss and Brookhart, 2009;Sadler, 2013;Lam, 2016;Othman et al, 2022;Emran et al, 2023). While teachers tend to favor assessment of learning, limited studies have reported formativeoriented beliefs and practices (Price et al, 2011;Coombs et al, 2020;DeLuca et al, 2021).…”
Section: Assessment Practicesmentioning
confidence: 99%
“…These practices involve providing feedback to modify and improve teaching and learning (assessment for learning), students' self and peer assessment (assessment as learning), and judging students' mastery at the end of the instructional period (assessment of learning) (Glazer, 2014;Yan and Brown, 2021;Baidoo-Anu et al, 2023a). Key assessment practices include effective questioning, sharing learning intentions and success criteria with students, and using summative assessment for formative purposes (Moss and Brookhart, 2009;Sadler, 2013;Lam, 2016;Othman et al, 2022;Emran et al, 2023). While teachers tend to favor assessment of learning, limited studies have reported formativeoriented beliefs and practices (Price et al, 2011;Coombs et al, 2020;DeLuca et al, 2021).…”
Section: Assessment Practicesmentioning
confidence: 99%